1973
DOI: 10.1111/j.1532-5415.1973.tb01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Rationale for Procaine (Gerovital H3) Therapy in Geriatrics: Inhibition of Monoamine Oxidase

Abstract: Gerovital H3, a specially formulated preparation of procaine hydrochloride, has been employed for several years in the treatment of various manifestations of aging. Heretofore, there has been no pharmacologic basis for its use in geriatric patients, although procaine hydrochloride and inhibitors of the enzyme, monoamine oxidase (MAO), are known to have many of the same pharmacologic actions. The relative effectiveness of Gerovital H3, commercial procaine hydrochloride (Novocain), and iproniazid as MAO inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The dilutional studies with pre‐incubated enzyme‐inhibitor complexes, as well as the other data, strongly indicate that GH3 is a reversible inhibitor of MAO, and that this inhibition is fully competitive as shown by the Lineweaver‐Burk and Dixon plots. These results, taken with the results of previous studies performed with GH3 (1, 2), show that GH3 is a weak (Ki 8.9 × 10 −5 ), reversible, fully competitive inhibitor of MAO. Robinson et al (16, 17) found an age‐dependent increase in MAO activity of human brain, plasma and platelets and a corresponding decrease in central monoamines.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The dilutional studies with pre‐incubated enzyme‐inhibitor complexes, as well as the other data, strongly indicate that GH3 is a reversible inhibitor of MAO, and that this inhibition is fully competitive as shown by the Lineweaver‐Burk and Dixon plots. These results, taken with the results of previous studies performed with GH3 (1, 2), show that GH3 is a weak (Ki 8.9 × 10 −5 ), reversible, fully competitive inhibitor of MAO. Robinson et al (16, 17) found an age‐dependent increase in MAO activity of human brain, plasma and platelets and a corresponding decrease in central monoamines.…”
Section: Discussionsupporting
confidence: 87%
“…The difference in the abilities of GH3 and iproniazid to inhibit M A 0 observed in previous studies (1) is of special interest since it may indicate that these two agents interact with the enzyme by different mechanisms. For example, iproniazid is an irreversible (6), mixed compet-…”
mentioning
confidence: 89%
See 3 more Smart Citations